2012
DOI: 10.1007/s11596-012-0066-y
|View full text |Cite
|
Sign up to set email alerts
|

CD151 promotes proliferation and migration of PC3 cells via the formation of CD151-integrin α3/α6 complex

Abstract: Over-expression of CD151 was found to be associated with metastasis and poor prognosis of prostatic carcinoma. This study was designed to examine the mechanism by which CD151 promotes the proliferation and migration of prostatic cancer cells. The pAAV-CD151, pAAV-GFP and pAAV-CD151-AAA mutant plasmids were constructed and used to transiently transfect PC3 cells (a prostatic carcinoma 3 cell line) by the mediation of Fugene HD. Then, the cells were assigned to control group, pAAV-GFP group, pAAV-CD151 group, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…This would be consistent with the recent demonstration that LM-511 promotes proliferation and partially blocks EMT in human β cells 80 . An interesting possibility is that these distinct LM-511 and LM-332-dependent adhesive responses during EMT and MET may be differentially regulated by CD151, an important modulator of LM-binding integrins 66 , 81 , 82 . CD151 overexpression was shown recently to be an independent prognostic marker of poor overall survival in invasive breast cancer, particularly in quintuple negative breast cancer, a subtype of TN breast cancer 83 .…”
Section: Conclusion and Future Perspectivessupporting
confidence: 89%
“…This would be consistent with the recent demonstration that LM-511 promotes proliferation and partially blocks EMT in human β cells 80 . An interesting possibility is that these distinct LM-511 and LM-332-dependent adhesive responses during EMT and MET may be differentially regulated by CD151, an important modulator of LM-binding integrins 66 , 81 , 82 . CD151 overexpression was shown recently to be an independent prognostic marker of poor overall survival in invasive breast cancer, particularly in quintuple negative breast cancer, a subtype of TN breast cancer 83 .…”
Section: Conclusion and Future Perspectivessupporting
confidence: 89%
“…It was reported that promigratory function of CD151 in PC3 cells was based on regulation of ERK activity (Yang et al, 2012). We additionally showed that presence of CD151 facilitates phosphorylation of FAK, Src and HSP27 (considered as directly involved in regulation of cell migration) in response to osteoblasts-conditioned medium.…”
Section: Discussionsupporting
confidence: 53%
“…Molecular studies involving CD151 with cancer progression and metastasis to date have focused on in vitro and grafting models. These studies have shown that knockdown/-out or mutation of CD151 decreases cell motility (16)(17)(18)(19)(20)(21)(22) and/or decreases experimental metastasis (23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%